Intelligent manufacturing - Underwood, Lynn (The EIU series., 1994)
Shows how the use of information technology can improve the manufacturing process without necessarily requiring large investment. The book discusses strategic planning on product and process enhancement, organizational change, managing people through the transformation and risk management.